AcMYB1 Interacts With AcbHLH1 to Regulate Anthocyanin Biosynthesis in Aglaonema commutatum - Li, Ji; Wu, Kunlin; Li, Lin; Ma, Guohua; Fang, Lin; Zeng, Songjun (Frontiers in Plant Science, 2022)
Aglaonema commutatum is one of the most popular foliage plants with abundant leaf phenotypes; therefore, anthocyanin coloration is a vital economic trait in A. commutatum. However, the molecular mechanisms underlying anthocyanin biosynthesis and its regulation remain unclear. In this study, AcMYB1 and AcbHLH1, transcription factor genes related to an R2R3-myeloblast (MYB) and a basic helix–loop–helix (bHLH), respectively, were isolated from A. commutatum “Red Valentine” and functionally characterized. AcMYB1 and AcbHLH1 were found to interact by Y2H and BiFC assay. AcMYB1 was grouped into the AN2 subgroup and shared high homology with the known regulators of anthocyanin biosynthesis. Gene expression analysis showed that both AcMYB1 and AcbHLH1 have similar expression patterns to anthocyanin structural genes and correlate with anthocyanin distribution in different tissues of A. commutatum. Light strongly promoted anthocyanin accumulation by upregulating the expression of anthocyanin-related genes in A. commutatum leaves. Ectopic expression of AcMYB1 in tobacco remarkably increased anthocyanin accumulation in both vegetative and reproductive tissues at various developmental stages. These results provide insights into the regulation of anthocyanin biosynthesis in A. commutatum and are useful for breeding new A. commutatum cultivars with enhanced ornamental value.